Analiza razlogov za sodelovanje v tekmovanju mladih športnih plezalcev - Perko, Uroš; Pišot, Rado (Revija za elementarno izobraževanje, 2014)
Analysis of Reasons for Participating in Competitions for Young Sport Climbers. The aim of the study was to determine, how young sports climbers evaluate reasons for participating in climbing competitions. For this purpose we interviewed 125 competitors of both genders, year of birth 2002 and younger. Children were participating in the competitions for East and West League in the youngest category. Data were collected with a closeended questionnaire. The acquired data were processed with SPSS software programme; frequencies were carried out. Mean age was 8.9 years. Most young athletes, 42.4%, attend competitions with the purpose of gaining new experience, followed by those whose main goal is good climbing. These are 40.8%. 14.4% attend competitions to achieve good result and 2.4% for reason of socializing. 19.2% of children don’t care if they don’t reach the top of the climbing route, but 80.8% are slightly to quite dissatisfied. The study shows that internal motivation is dominant in young climbers. Mostly they attend competitions to gain new experience and to show good climbing. If they don’t reach the top of the climbing route, they leave competition unsatisfied. It would be reasonable to consider the study results in the organization of competitions for youngest categories.